"Drop dead … I need your job": An exploratory study of intra-professional conflict amongst nurses in two Ontario cities. (April 2016) - Boateng, Godfred O.; Adams, Tracey L.
Abstract: Past studies have focused on inter-professional conflict and its implication for professional status and work. However, there is a dearth of research on intra-professional conflict and its implications for professions. This study explores intra-professional conflicts among nurses in Ontario, using a qualitative research design, drawing on in-depth interviews with 66 nurses. The study identifies conflicts along race and age: Visible minority and younger nurses report more conflict, with visible minority nurses particularly vulnerable and racially marginalized. Members of Visible minorities and young nurses responded to workplace conflict by demonstrating competence, seeking support from colleagues, and either ignoring the abuse or standing up for themselves. These strategies do nothing to challenge professional unity. Nonetheless, intra-professional conflict has negative consequences for professionals and their work. Highlights: Intra-professional conflicts occur in nursing along the lines of race and age. Visible minority nurses are vulnerable to bullying, discrimination and incivilities. Young nurses experience bullying and are more prone to workplace incivilities. Competence building, social support and assertiveness mitigate conflicts in nursing. While conflicts may not weaken professional unity, they undermine professional work.